Real-world effectiveness of Yindan Jiedu granules-based treatment on patients infected with the SARS-CoV-2 Omicron variants BA.2 combined with high-risk factors: A cohort study - Feng, Ying; Liu, Yao; Liu, Long; Liu, Yao; Jiang, Yuyong; Hou, Yixin; Zhou, Yang; Song, Rui; Chen, Xiaoyou; Wang, Xianbo (Frontiers in Pharmacology, 2022)
Background: Our previous studies have shown that Yindan Jiedu granules (YDJDG) can effectively treat coronavirus disease 2019 (COVID-19); however, the high infectivity and the immune escape potential of the Omicron variant BA.2 make it more difficult to control, and patients with high-risk factors prone to progress rapidly. Purpose: To evaluate YDJDG’s efficacy in treating patients with the Omicron variant BA.2 with high-risk factors and compared it with that of Paxlovid. Methods: A total of 257 patients who fulfilled the inclusion criteria were allocated to the YDJDG (115 cases), Paxlovid (115 cases), and control (27 cases) groups. A Cox regression model was used to analyze the independent factors affecting the shedding time of nucleic acid in 14 days. Propensity score matching (PSM) was used to match the characteristics of individuals in the three groups, while the Kaplan-Meier method was used to compare the shedding proportion of nucleic acids. Results: Cox analysis showed that the vaccine booster (p = 0.006), YDJDG treatment (p = 0.020), and Paxlovid treatment (p < 0.0001) were independent predictors of nucleic acid shedding at 14 days. The median recovery time was 11.49 days in the YDJDG group, 10.21 days in the Paxlovid group, and 13.93 days in the control group. After PSM (3:1), the results showed that the nucleic acid shedding time of the YDJDG group (n = 53) was 2.47 days shorter than that of the control group (n = 21) (p = 0.0076), while the Paxlovid group (n = 44) had a 4.34 days shorter than that of the control group (n = 17) (p < 0.0001). After PSM (1:1), YDJDG and Paxlovid (76 pairs) were also analyzed. In the YDJDG group, nucleic acid shedding time was 1.43 days longer than that observed in the Paxlovid group (p = 0.020). At 10 and 14 days, the Paxlovid group showed a significant difference in the nucleic acid shedding proportion compared with the control group (p = 0.036, p = 0.0015). A significant difference was also observed between the YDJDG and control groups (p = 0.040) at 14 days. Conclusion: As a safe and convenient oral drug, YDJDG can be used as an alternative to antiviral therapy for such patients.